Moving from the margins: Life histories on transforming the study of racism - Andersen, Margaret L.; Zinn, Maxine Baca 1942- (Stanford, California: Stanford University Press, 2024)
"At a time when movements for racial justice are front and center in U.S. national politics, this book provides essential new understanding to the study of race, its influence on people's lives, and what we can do to address the persistent and foundational American problem of systemic racism. Knowledge about race and racism changes as social and historical conditions evolve, as different generations of scholars experience unique societal conditions, and as new voices from those who have previously been kept at the margins have challenged us to reconceive our thinking about race and ethnicity. In this collection of essays by prominent sociologists whose work has transformed the understanding of race and ethnicity, each reflects on their career and how their personal experiences have shaped their contribution to understanding racism, both in scholarly and public debate. Merging biography, memoir, and sociohistorical analysis, these essays provide vital insight into the influence of race people's perspectives and opportunities both inside and outside of academia, and how racial inequality is felt, experienced, and confronted"--
Includes bibliographical references and index.
Keywords: Racism -- Study and teaching (Higher) -- United States; Sociology; Race -- Study and teaching (Higher) -- United States; Race relations -- Study and teaching (Higher) -- United States; Sociologists -- United States -- Biography; Minority college teachers -- United States -- Biography; Autobiographies